(untitled) (Journal of Analytical Oncology, 2012)
Nodular lymphocyte predominant Hodgkin lymphoma (NLPHL) is a rare type of B-cell lymphoma with good prognosis and distinct clinicopathologic features. The hallmark histological feature is the presence of malignant lymphocyte predominant (LP) cells embedded within nodules predominantly composed of small B-lymphocytes. Immunoarchitectural variations from these classic nodules could occur. The clinical and pathological significance of NLPHL with variant patterns is, however, uncertain and controversial. Some oncologists and pathologists consider variant atypical nodules to represent a simple localized overgrowth of the LP cells without significant pathological or clinical implications. Other oncologists, however, suggest that they might represent a different biological behavior in the form of intranodal progression with early transformation into large B-cell lymphoma. Therefore, NLPHLs with variant atypical patterns represent a more aggressive clinical course and an indicator of a higher risk of recurrence that warrants a more aggressive treatment even in the early stages. We performed a retrospective review study to investigate the prevalence and importance of atypical nodules in NLPHL. We found seven cases of NLPHL, three (43%) of which showed variant patterns with different immunoarchitectural features from the classic nodules of NLPHL. We did not find clinical or prognostic differences between the two groups of classic nodules of NLPHL and atypical variant nodules of NLPHL. The significance of which, however, cannot be drawn from this small case series. Therefore, further larger scale studies are warranted. In addition, pathologists should be aware of this phenomenon to avoid overcalling these cases as high-grade lymphomas.